All i want for christmas eaudiobook - Loggia, Wendy (Listening Library, 2020)
A sweet Christmas romance about a girl with one wish: to kiss someone under the mistletoe. The holiday escape you need! Bailey Briggs is counting down the days to Christmas: she lives for holiday music, baking cookies, going on snowy sleigh rides, and wearing her light-up reindeer ears to work at Winslow's bookstore. But all she really wants this year is the one thing she doesn't have: someone special to kiss under the mistletoe. And she's 100 percent certain that that someone isn't Jacob Marley—athlete, player, and of questionable taste in girlfriends—and that Charlie, the mysterious stranger with the British accent, is the romantic lead of her dreams. Is she right? This will be a December to remember, filled with real-life Christmas magic . . . and, if she stays on Santa's nice list, a wish that just might come true.  "It's all very adorable." —Buzzfeed Want more holiday romance? Pick up New Year's Kiss by Lee Matthews , an Underlined romance set at a snowy Vermont lodge about two sisters, one cute boy, and an epic bucket list!